Pengaruh Layanan Bimbingan Kelompok Teknik Sosiodrama Terhadap Kemampuan Hubungan Interpersonal Di Panti Asuhan Al-Ghasyiyah Bathin Solapan Duri Riau - Nisa Ullya; Dodi Pasila Putra; Muhiddinur Kamal; Fadhilla Yusri (Jurnal Bintang Pendidikan Indonesia, 2023)
This research departs from the phenomenon of interpersonal relationships that are owned by the children of the Al-Ghasyiyah Orphanage which are still low and medium, this is marked by the orphans who do not know each other closely, do not understand each other's personal characteristics, are not familiar, lack of cooperation, orphans they still lack the courage to express their ideas or opinions, there are still social conflicts between them, they close themselves off because they lack confidence in getting along with other orphans, they lack a sense of initiative in making friends and working together. Researchers try to provide group guidance services with sociodrama techniques to orphanages to improve interpersonal relationships, the goal to be achieved in this study is to find out whether or not there are significant differences in the interpersonal relationships of orphanage children before and after being given sociodrama technique group guidance services, as well as effective whether or not the sociodrama technique group guidance services to improve the interpersonal relations skills of orphans at the Al-Ghasyiyah Bathin Solapan Duri Orphanage, Riau. This research is classified as a pre-experimental study using a one group pretest posttest design. The population in this study was the adolescent children of the Al-Ghasyiyah Bathin Solapan Duri Orphanage, Riau. The population is young women at the Al-Ghasyiyah Bathin Solapan Duri Riau Orphanage, totaling 20 people. The sample is adolescents who are indicated to have a poor level of interpersonal relations, namely 8 people, sampling based on purposive sampling technique. The instrument used was a Likert scale questionnaire. Data analysis used non-parametric statistical tests using the Wilcoxon signed rank test method with the help of Statistical Product and Service Solutions (SPSS) version 20.00. pretest and posttest. From the results of the Wilcoxon test calculation, a significant p-value of 0.011 < α (α = 0.05) is obtained, which means that Ha is accepted and Ho is rejected. From the results of the calculation of the Wilcoxon test, it can be interpreted that the interpersonal relationship skills of the orphans increased after being given treatment, namely the sociodrama technique Group Guidance Service.